Cross-border acquisition or greenfield investment? The role of investor sentiment - Dong, Li; Chen, Jinlong (Frontiers in Psychology, 2023)
This paper empirically studies the impact of investor sentiment on the establishment mode of firm outward foreign direct investment (OFDI). Based on the data of Chinese listed companies between 2007 and 2019, we show that firms prefer cross-border acquisition over greenfield investment when investor sentiment is high, and equity issuance and catering to sentiment are transmission channels. Cross-sectional test results show that the impact of investor sentiment on the establishment mode is concentrated in non-state-owned enterprises, and is stronger in non-eastern province firms and in technology-intensive OFDI. After various robustness tests, the main conclusion remains unchanged. This paper not only finds a new determinant that affects the establishment mode of OFDI but also enriches the research on the economic consequences of investor sentiment, which helps understand the role of investor sentiment in firms’ internationalization decisions.